Pedestrian Volume Characteristic in the Commercial Area in Yogyakarta - Muttaqin, Muchammad Zaenal (2022)
Pedestrians are different from vehicles. Pedestrian has its unique characteristic, especially for its flexibility in traffic. Pedestrians play an important role in supporting sustainable roads as the impact from the vehicle such as pollution, even crowded vehicles create more problems than pedestrians. Pedestrians' characteristics can be divided based on their activity, area, and even based on their behaviour when they are walking. All pedestrian management policies must be started from knowing local and then global characteristics. This will serve more details about pedestrian lanes, and can also be used to derive fundamental parameters for pedestrian operations and to create pedestrian models. In traffic research, one of the volume functions related to speed and density was also used to pre-analyze pedestrian behaviour. The purpose of this study was to introduce the local characteristic of pedestrians in Yogyakarta as a basic term for making regulations or policies as well as better planning for pedestrian lanes. The results showed that pedestrian volume had different characteristics between morning flow and afternoon flow. The characteristic volume of the morning flow tended to decrease due to the difference in temperatures which was lower in the morningandhigher temperatures during the day. As for the afternoon flow, pedestrian fluctuations increased duetothe temperatures decreasefromnoonto evening. This was reinforced byan independent T test. Another result showed that pedestrians groupsdominated the shopping area, hospital area, as well as public space. Lastly, the characteristics ofpedestriansin the sidewalk commercial areaalsohad different characteristicsin terms of carrying goods, whereas the shopping areasweremoredominatedbypedestrianscarrying goodsthan others. These basic terms were expected to be the basic foundation for managing and planning pedestrian lanes based on their local characteristics. © Published under licence by IOP Publishing Ltd.